Could smart research ensure healthy people in disrupted cities?. (December 2020) - Giles-Corti, Billie; Zapata-Diomedi, Belen; Jafari, Afshin; Both, Alan; Gunn, Lucy
Abstract: Background: Since the late 19th century, city planners have struggled to cope with new types of urban transport and mobility that threatened the existing system, or even rendered it obsolete. Purpose: As city planners confront the range of disruptive urban mobilities currently on the horizon, this paper explores how we can draw on a vast body of evidence to anticipate and avoid unintended consequences to people's health and wellbeing . Methods: This commentary involved a rapid review of the literature on transport disruption. Results: We found that to avoid the unintended consequences of disruption, research, policy and practice must think beyond single issues (such as the risk of chronic disease, injury, or traffic management) and consider the broader consequences of interventions. For example, although autonomous vehicles will probably reduce road trauma, what will be the negative consequences for physical inactivity, sedentary behavior, chronic disease, land use, traffic congestion and commuting patterns? Research is needed that considers and informs how to mitigate the range of potential harms caused by disruptive mobilities. Conclusion: In the face of new disruptive mobilities, we must: (a) draw on existing evidence to shape new regulations that address the 'who, when and where' rules of introducing new mobilities (such as electric assisted bicycles (e-bikes) and scooters (e-scooters)) of which the health repercussions can be easily anticipated; (b) monitor and evaluate the implementation of any interventions through natural experiment studies; and (c) use innovative research methods (such as agent-based simulation and health-impact-assessment modelling) to assess the likely effects of emerging disruptive mobilities (e.g., autonomous vehicles) on health and wellbeing and on the environment. Highlights: Urban mobility disruptions are not new. Without regulation over new disruptive mobilities, avoidable harm is inevitable. Rules addressing the 'who, when and where' of introducing new mobilities is needed. A century of evidence should be used to inform current policy and practice. Simulation research and natural experiments can simulate and evaluate health effects.